Georgia : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2014)
This paper discusses findings of the Financial System Stability Assessment for Georgia. Georgia has weathered several shocks, but still faces a number of important risks. The economy has withstood well the conflict with Russia, the global financial crisis, and domestic political uncertainty. Significant steps have been taken to strengthen banking regulation and supervision, which exhibit a very high degree of compliance with international standards. The National Bank of Georgia has also introduced an advanced risk-based supervisory regime while maintaining a conservative approach aimed at detecting vulnerabilities at an early stage, and allocating supervisory resources in the most efficient and effective manner.